Zinc and iron oxide nanoparticles improved the plant growth and reduced the oxidative stress and cadmium concentration in wheat. (January 2019) - Rizwan, Muhammad; Ali, Shafaqat; Ali, Basharat; Adrees, Muhammad; Arshad, Muhammad; Hussain, Afzal; Zia ur Rehman, Muhammad; Waris, Aisha Abdul
Abstract: The effects of seed priming with zinc oxide (ZnO) and iron (Fe) nanoparticles (NPs) on the growth and cadmium (Cd) accumulation by wheat ( Triticum aestivum ) were investigated. Seeds of wheat were primed with different concentrations of either ZnO NPs (0, 25, 50, 75, and 100 mg L −1 ) or Fe NPs (0, 5, 10, 15, and 20 mg L −1 ) for 24 h by continuous aeration and then the seeds were sown in a soil which was contaminated with Cd due to long-term application of sewage water. Plants were grown till maturity under natural conditions with 60–70% moisture contents of total soil water holding capacity throughout the experiment. Plant height, spike length, and dry weights of shoots, roots, spikes, and grains were increased with NPs, in particular with the higher rates of NPs. The results depicted that NPs positively affected the photosynthesis of wheat as compared to the control. The NPs reduced the electrolyte leakage and superoxide dismutase and peroxidase activities in leaves of Cd-stressed wheat. The concentrations of Cd in roots, shoots, and grains were significantly decreased with NPs application. The Cd content in the grains was below the threshold level of Cd (0.2 mg kg −1 ) for cereals when the seeds were treated with higher NPs treatments. The application of ZnO NPs increased the Zn concentrations and Fe NPs increased the Fe concentrations in roots, shoots, and grains. Overall, the NPs play a major role in the increase in biomass, nutrients and decrease in Cd toxicity in wheat. Highlights: Nanoparticles (NPs) of zinc and iron increased the wheat growth under cadmium (Cd) stress. Both NPs increased chlorophyll contents and gas exchange attributes in Cd-stressed plants. Both NPs reduced the oxidative stress in plants. Both NPs decreased Cd concentrations while enhanced Fe and Zn concentrations in wheat.